Correction to: Assessment of treatment responses in children and adolescents with Ewing sarcoma with metabolic tumor parameters derived from 18F-FDG-PET/CT and circulating tumor DNA (European Journal of Nuclear Medicine and Molecular Imaging, (2019), 10.1007/s00259-019-04649-1) - Schmidkonz, Christian; Krumbholz, Manuela; Atzinger, Armin; Cordes, Michael; Götz, Theresa; Prante, Olaf; Ritt, Philipp; Schaefer, Christiane; Agaimy, Abbas; Hartmann, Wolfgang; Roessig, Claudia; Froehlich, Birgit; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2020)
The original version on this paper contained an error. The author names, though correctly appeared in the PDF version, were incorrectly displayed in indexing sites. This error occurred because of the incorrect tagging of their names in themetadata of this article. The purpose of this Erratum is the correction of metadata. Therefore, indexing sites should now reflect their names as Schmidkonz C, Krumbholz M, Atzinger A, Cordes M, Goetz TI, Prante O, Ritt P, Schaefer C, Agaimy A, Hartmann W, Rössig C, Fröhlich B, Bäuerle T, Dirksen U, Kuwert T, Metzler M. The original article has been corrected.
CRIS-Team Scopus Importer:2020-02-25